29 Development of minimally invasive mitral repair program. (5th October 2017) - Tolan, M; Ryan, E; Obadia, JF; McCarthy, J
Abstract : Introduction: Setting up a minimally invasive approach to mitral valve repair requires a mentored approach and team work of all personnel involved. Prior to program commencement the surgical team had site visits to an international centre of excellence. Methods: Over the last year, we have subsequently undertaken mitral repair using a thoracoscopic approach in 22 patients. Their ages ranged from 27 to 86 years, (11 male, 11 female) with a mean age 60 years. A specialist surgeon, experienced in minimally invasive mitral surgery was present at all cases. Results: All patients had a successful mitral repair performed. One patient required conversion to full sternotomy. One patient had an abdominal bleed requiring interventional radiology coiling of the source artery. There were no re-operations and no patient required dialysis. On echo all patients had no, trivial or mild mitral regurgitation. There was 0% mortality and no peri-operative case of CVA or other major mobidity. Conclusions: Minimally invasive mitral valve repair is a feasible and beneficial option in mitral surgery. It has a learning curve and team training and proctoring are essential when developing it in a surgical unit. It has the potential to enhance patient care in a select group of patients.